Classes of Ordinary Differential Equations for the Alpha Power Lomax Distribution - Mahariq, Ibrahim; Saeed, Noor; Khalil, Alamgir; Ijaz, Muhammad (Contemporary Mathematics, 2024)
This paper focuses on the ordinary differential equations (ODEs) of the alpha-power Lomax distribution. The ODEs are derived from the alpha-power Lomax (APL) distribution for the density, quantile, survival and hazard functions. These ODEs helps to study the shape of various functions that describe the probability distribution. Under necessary conditions of the parameters, the existence of the ODEs is possible and obtained.